Enhancing Bus Body Assembly Efficiency: Comparative Analysis of Ranked Positional Weight and Region Approach at PT. ABC - Herry Dwi Prasetyo; Joumil Aidil (Advance Sustainable Science Engineering and Technology, 2024)
In general line balancing problems occur in assembling industries compared to manufacturing industries. Problems that often occur on a production line can usually be seen from the presence of a high work in process bottleneck. The problem faced by the company in the production process is the level of efficiency of the workforce and production machines which are still less than optimal, due to the imbalance of the workload between work stations caused by delays in materials from the warehouse, then the operator usually waits for directions from the foreman first, then waits for the material processing process from other station. Therefore, in the bus body assembly process, it is necessary to make an analysis or calculation of the balance of the bus body assembly process so that it can run smoothly. In the line balancing study using the ranked positional weight and region approach methods, the results of the ranked positional weight method for the bus body assembly line efficiency were 78.43%, then for the balance delay of the bus body assembly 21.57% and idle time 1189.16 minutes. After data processing using the region approach method for the bus body assembly line efficiency, the results were 64.84%, then for the balance delay of the bus body assembly 35.16% and idle time 2344.75 minutes